Christopher Fry - Stanford, Derek (Writers and their work., 1962)
'The mainspring of Fry's work', says Derek Stanford in this informed appreciation, 'is his intuition of the presence of mystery.' Stanford's analysis of the plays is shrewd and thorough. He sets his subjects against the background of his time - particularly the contemporary theatre - and provides the reader with enough of the facts of Fry's life to enhance understanding of his outlook. Christopher Fry's plays, particularly The Lady's Not for Burning.